The Influence of Green Product, Green Awareness, and Evironmental Concern on Green Purchase Intention on Garnier Products in The Meruya Area - Raihan, Ahmad; Ramli, Yanto (ARE Publisher, 2024)
This research is to analyze the influence of green products, green awareness, environmental concern on green purchase intention for Garnier products. The population object in this research is people in the Meruya area, West Jakarta. This research was conducted on 165 respondents using a quantitative descriptive approach. Determination of sample size using convenience sampling technique. The data collection method uses a survey method, with the research instrument being a questionnaire. The approach used in this research is the Structural Equation Model (SEM) with the Smart-PLS analysis tool. This research is to prove that green products have a significant effect on green purchase intention, green awareness has a significant and positive effect on green purchase intention, and environmental concern has a positive and significant effect on green purchase intention.